Playing with fire [videorecording (DVD)] - Fickman, Andy; Cena, John; Key, Keegan-Michael, 1971-; Leguizamo, John (Paramount, 2019)
Three firefighters suddenly have their hands full when they rescue a trio of rambunctious kids.